Problems Of Development Of Mass Sports And Health Work In General Education Schools (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
The article addresses the problems of the development of mass sports in general educational institutions, as well as low physical activity and weak physical development of schoolchildren. The formation of interest in sports activity of schoolchildren through the national system of continuous sports competitions is proposed.